2012
DOI: 10.1038/cr.2012.20
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-induced posttranslational activation of protein phosphatases PP2A and PP1 in yeast

Abstract: The protein phosphatases PP2A and PP1 are major regulators of a variety of cellular processes in yeast and other eukaryotes. Here, we reveal that both enzymes are direct targets of glucose sensing. Addition of glucose to glucose-deprived yeast cells triggered rapid posttranslational activation of both PP2A and PP1. Glucose activation of PP2A is controlled by regulatory subunits Rts1, Cdc55, Rrd1 and Rrd2. It is associated with rapid carboxymethylation of the catalytic subunits, which is necessary but not suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 91 publications
7
84
0
Order By: Relevance
“…Since ceramide production is controlled by TORC2-dependent signals, this observation strengthens previous genetic data that suggested a role for Rts1 in a ceramide-dependent feedback loop that negatively regulates TORC2 signaling (Lucena et al 2018). Rts1 hyperphosphorylation in poor carbon is correlated with a decrease in Rts1-associated phosphatase activity, consistent with a previous study that suggested that a fraction of Rts1 dissociates from PP2A in poor carbon (Castermans et al 2012). A previous study suggested that the Rts1 that dissociates from PP2A in poor carbon could have PP2A-independent functions.…”
Section: Elm1 and The Gin4-related Kinases Do Not Influence Torc2 Sigsupporting
confidence: 80%
See 3 more Smart Citations
“…Since ceramide production is controlled by TORC2-dependent signals, this observation strengthens previous genetic data that suggested a role for Rts1 in a ceramide-dependent feedback loop that negatively regulates TORC2 signaling (Lucena et al 2018). Rts1 hyperphosphorylation in poor carbon is correlated with a decrease in Rts1-associated phosphatase activity, consistent with a previous study that suggested that a fraction of Rts1 dissociates from PP2A in poor carbon (Castermans et al 2012). A previous study suggested that the Rts1 that dissociates from PP2A in poor carbon could have PP2A-independent functions.…”
Section: Elm1 and The Gin4-related Kinases Do Not Influence Torc2 Sigsupporting
confidence: 80%
“…Phosphatase activity associated with Rts1 was reduced in cells growing in poor carbon, when Rts1 was hyperphosphorylated ( Figure 3E). A previous study found that PP2A dissociates from Rts1 when cells are grown in poor carbon, which could explain the reduction in Rts1-associated phosphatase activity in those conditions (Castermans et al 2012). Further evidence for dissociation of the PP2A Rts1 complex in poor carbon came from analysis of Rts1 phosphorylation in response to inactivation of PP2A catalytic subunits.…”
Section: Pp2a Rts1 Is Controlled By Nutrientsmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of glucose to a yeast culture growing in its absence activates the GLC7-and SIT4-encoded protein phosphatases (54). The effect of glucose on their activation is rapid, occurring in less than 1 min and acts through a G-proteincoupled receptor.…”
Section: Discussionmentioning
confidence: 99%